Training microcyle planning specifics in multiannual training systems at football sport reserve academies - Antipov, A. V.; Kulishenko, I. V.; Guba, V. P. (Theory and Practice of Physical Culture, 2019)
The article analyzes the modern training microcycle planning concepts for the U16-17, U13-15 and U10-12 age groups tested by the Locomotive Football Academy (Moscow). The study was designed to develop practical grounds for the age-specific training microcycle planning versions with special combinations of traditional and special warm-up and wrap-up and the physical, technical and tactical training tools; with a special priority to the training workloads and recreation in every stage of a yearly training cycle. The study data and analyses showed that the football reserve training microcycle planning shall be customized to the individual aging and biological maturing process stages, challenges and requirements. Training systems for the senior groups shall be focused on the special physical fitness and teamwork improvement practices; whilst the lower-skilled group trainings shall make an emphasis on the individual skills and teamwork. The beginner trainings shall assign more time for rest in the middle and final periods of each training microcycle; and the skilled footballers shall be given rest next day after every match